Nitrogen fixation: key genetic regulatory mechanisms. (1st February 2005) - Martinez-Argudo, I.; Little, R.; Shearer, N.; Johnson, P.; Dixon, R.
Abstract : The necessity to respond to the level of fixed nitrogen and external oxygen concentrations and to provide sufficient energy for nitrogen fixation imposes common regulatory principles amongst diazotrophs. The NifL–NifA system in Azotobacter vinelandii integrates the signals of redox, fixed-nitrogen and carbon status to regulate nif transcription. Multidomain signalling interactions between NifL and NifA are modulated by redox changes, ligand binding and interaction with the signal-transduction protein GlnK. Under adverse redox conditions (excess oxygen) or when fixed nitrogen is in excess, NifL forms a complex with NifA in which transcriptional activation is prevented. Oxidized NifL forms a binary complex with NifA to inhibit NifA activity. When fixed nitrogen is in excess, the non-covalently modified form of GlnK interacts with NifL to promote the formation of a GlnK–NifL–NifA ternary complex. When the cell re-encounters favourable conditions for nitrogen fixation, it is necessary to deactivate the signals to ensure that the NifL–NifA complex is dissociated so that NifA is free to activate transcription. This is achieved through interactions with 2-oxoglutarate, a key metabolic signal of the carbon status, which binds to the N-terminal GAF (cG MP-specific and stimulated phosphodiesterases, A nabaena adenylate cyclases and Escherichia coli F hlA) domain of NifA.